The role of women in scientific research - Nguyễn Thị Huyền (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Women have always played an important role in the socio-economic development of any country in the world.  With scientific research activities, female scientists have also confirmed their roles.  Within the framework of the article, the author will analyze the role of women in scientific research and propose some solutions to enhance the role of women in the glorious but also difficult field of scientific research.  challenges at work, family and society.